Mobile health application adoption and service performance in Indonesian private hospitals: A JASP-compatible panel data study - Sahara Putri Dahlan (Health Economics Insights Journal, 2026)
Mobile health applications have become a visible component of Indonesia's hospital digital transformation; however, management research still has limited longitudinal evidence on how hospital-level readiness factors translate into adoption and service outcomes. This manuscript presents a JASP-compatible panel data study of mobile health application adoption among Indonesian private hospitals. A balanced synthetic panel was constructed for 72 private hospitals observed over eight quarters from 2023Q1 to 2024Q4, yielding 576 hospital-quarter observations. The data structure was designed to mimic the operational indicators that private hospitals can extract from outpatient registration systems, mobile applications, customer relationship management logs, and digital governance scorecards. Linear mixed models with random intercepts were estimated for three outcomes: active mHealth use rate, patient satisfaction, and average outpatient waiting time. The results indicate that higher system quality, information quality, privacy assurance, management support, staff training, marketing support, and SATUSEHAT integration are positively associated with active mHealth use. Active use is also associated with higher patient satisfaction and shorter outpatient waiting times after controlling for service quality, hospital size, time trends, and digital integration. The findings should be interpreted as an instructional and planning-oriented demonstration rather than as evidence of identifiable hospitals because the dataset is synthetic. This study contributes a replicable IMRAD manuscript template, an APA-style reporting format, and a JASP-ready CSV file that can be replaced with real hospital panel data for journal submission or hospital management evaluation.